Recent Findings on Cell-Based Therapies for COVID19-Related Pulmonary Fibrosis. (7th April 2021) - Chuang, Hong-Meng; Ho, Li-Ing; Harn, Horng-Jyh; Liu, Ching-Ann
COVID-19 has spread worldwide, including the United States, United Kingdom, and Italy, along with its site of origin in China, since 2020. The virus was first found in the Wuhan seafood market at the end of 2019, with a controversial source. The clinical symptoms of COVID-19 include fever, cough, and respiratory tract inflammation, with some severe patients developing an acute and chronic lung injury, such as acute respiratory distress syndrome (ARDS) and pulmonary fibrosis (PF). It has already claimed approximately 300 thousand human lives and the number is still on the rise; the only way to prevent the infection is to be safe till vaccines and reliable treatments develop. In previous studies, the use of mesenchymal stem cells (MSCs) in clinical trials had been proven to be effective in immune modulation and tissue repair promotion; however, their efficacy in treating COVID-19 remains underestimated. Here, we report the findings from past experiences of SARS and MSCs, and how SARS could also induce PF. Such studies may help to understand the rationale for the recent cell-based therapies for COVID-19.